2002
DOI: 10.1108/13552510210420577
|View full text |Cite
|
Sign up to set email alerts
|

Strategic dimensions of maintenance management

Abstract: The contemporary business environment has raised the strategic importance of the maintenance function in organizations which have significant investment in physical assets. Four strategic dimensions of maintenance management are identified, namely service‐delivery options, organization and work structuring, maintenance methodology and support systems. The alternatives available are reviewed: the guidelines for selection of these alternatives, the key decision areas in each of the four dimensions, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
275
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(288 citation statements)
references
References 10 publications
2
275
0
11
Order By: Relevance
“…Tsang [4] concluded that the strategic decisions to be taken with respect to the organisational design and structuring of maintenance activities include: (i) plant purpose, (ii) workforce location, and (iii) composition and flexibility of their workforce. The associated decisions require considering workload characteristics; plant location; cost of non-availability; skills and knowledge required; production policy; and human-resources policy.…”
Section: Organisation and Work Structuringmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsang [4] concluded that the strategic decisions to be taken with respect to the organisational design and structuring of maintenance activities include: (i) plant purpose, (ii) workforce location, and (iii) composition and flexibility of their workforce. The associated decisions require considering workload characteristics; plant location; cost of non-availability; skills and knowledge required; production policy; and human-resources policy.…”
Section: Organisation and Work Structuringmentioning
confidence: 99%
“…reduce the cost of unreliability. Recent developments [4] are: -♦ Emerging operational strategies. The economy-of-scale concept is losing some of its advocates.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can improve operational efficiency, risk levels and continuity (Janssen et al, 2009;Tsang, 2002). Costs (monetary expenditure, time, environmental impact/eco-footprint, and transaction costs) are incurred for categories such as personnel management, acquisition, operation and maintenance of assets, facility management, stock keeping, logistics, and procurement.…”
Section: Sustaining Operations and Reducing Stakeholder Costsmentioning
confidence: 99%
“…Activities can be dynamically divided between suppliers and customers to make the best use of capabilities and resources (Gebauer et al, 2011;Rollins et al, 2011). They may take over some of their customers' business processes (Vendor Managed Inventory; Collaborative Planning, Forecasting and Replenishment (CPFR); Vendor Stocking (Bloch, 2013)), or some echelons (levels) of maintenance (Sherbrooke, 2004;Tsang, 2002). Suppliers and customer can ex ante synchronize their ordering-delivery cycles to optimize supplier operations ( Van der Vlist, 2004;Van Fenema and Koeiman, 2003).…”
Section: Iss and Value Chains: A Taxonomymentioning
confidence: 99%